Discrete Cu-Metalloporous Polycarbazole as a Nanoelectromediator for Effective Electrocarboxylation of Benzyl Bromide with CO2 - Boro, Bishal; Kalita, Priyanka; Vijayaprabhakaran, Aathilingam; Dao, Duy Quang; Nandy, Subhajit; Chae, Keun Hwa; Nailwal, Yogendra; Kathiresan, Murugavel; Mondal, John (American Chemical Society, 2023)
The electrochemical fixation of carbon dioxide (CO2) into organic halides is one of the most prominent strategies for mitigating atmospheric CO2 emission, along with the difficulties associated with the toxic and carcinogenic halogenated compounds. Cu-based nanomaterials have been explored for numerous applications in nanotechnology, including electrocatalysis, organic catalytic transformations, and photocatalysis. In this work, we have designed and developed a Cu-embedded carbazole-derived porous organic polymer (Cu@Cz-POP) nanohybrid by utilizing the Friedel？Crafts alkylation approach and employing 1,4-dimethoxybenzene as the cross-linking agent comprising unique characteristic features of the extended π-conjugated system along with an active metal center with tunable electrochemical properties. The Brunauer？Emmett？Teller surface area of the conjugated Cz-POP is found to be 1060 m2 g？1. The X-ray photoelectron spectroscopy (XPS) study demonstrates the formation of CuO nanoparticles in the polymeric framework. X-ray absorption fine structure analysis (EXAFS) also reveals the existence of CuO with a smaller fraction of Cu in the polymeric framework, which is corroborated with the XPS analysis. The Cu@Cz-POP nanohybrid is fabricated by drop-casting over a Ni foam, showing promising electrocatalytic activity toward electrocarboxylation of benzyl bromide in 0.1 M TBA·BF4/CH3CN with saturated CO2 medium with a current density of 120 mA cm？2 delivering 65% yield of phenylacetic acid (PAA) as the primary product along with traces of benzyl 2-phenylacetate (BPA) and 1,2-diphenylethane (DPE), and the turnover frequency is found to be 8.556 × 10？7 s？1. Density functional theory calculations demonstrate that CuO is adsorbed more favorably at the N1 nitrogen atom of Cz-POP. An electron transfer from the N1 atom and the aromatic rings of Cz-POP to the CuO center is observed and confirmed by the overlap of alpha orbitals.